Integrating Gender Analysis in Coastal Communities into Environmental Health Risk Assessment: Household Hygiene Behaviour - Handayani, Wahyu (Jurnal EnviScience (Environment Science), 2026)
Environmental Health Risk Assessment (EHRA) is widely used to evaluate environmental exposure and related health risks, yet most applications assume households as homogeneous units and rarely consider gender-differentiated exposure pathways. In coastal communities—characterized by saline intrusion, inadequate sanitation, flooding, and climate-related stressors—household hygiene practices are strongly shaped by gendered divisions of labor. This literature review synthesizes recent peer-reviewed studies to examine how gender roles influence exposure patterns within household hygiene practices in coastal settings. A thematic analysis was conducted to identify differential exposure pathways, risk distribution, and structural determinants affecting women and men. The review reveals that women, as primary managers of water, sanitation, and caregiving tasks, face higher frequency and duration of exposure to microbiological and chemical hazards, while men’s exposure is more commonly linked to infrastructure-related or occupational activities. Conventional EHRA frameworks rarely disaggregate exposure by gender, potentially underestimating intra-household risk variability. Integrating gender analysis into EHRA improves the accuracy of risk characterization and supports more equitable environmental health interventions in vulnerable coastal communities. Keywords: Environmental Health Risk Assessment; Gender; Coastal Sanitation; Household Hygiene; Exposure Pathways.